Neurodevelopmental outcomes of preterm infants conceived by assisted reproductive technology - Roychoudhury, Smita; Lodha, Abhay; Synnes, Anne; Abou Mehrem, Ayman; Canning, Roderick; Banihani, Rudaina; Beltempo, Marc; Theriault, Katherine; Yang, Junmin; Shah, Prakesh S.; Soraisham, Amuchou S.; Ting, Joseph; et al. (American journal of obstetrics and gynecology, 2021)
There have been concerns about the development of children conceived through assisted reproductive technology. Despite multiple studies investigating the outcomes of assisted conception, data focusing specifically on the neurodevelopmental outcomes of infants conceived through assisted reproductive technology and born preterm are limited. This study aimed to evaluate and compare the neurodevelopmental outcomes of preterm infants born at <29 weeks’ gestation at 18 to 24 months’ corrected age who were conceived through assisted reproductive technology and those who were conceived naturally. This retrospective cohort study included inborn, nonanomalous infants, born at <29 weeks’ gestation between January 1, 2010, and December 31, 2016, who had a neurodevelopmental assessment at 18 to 24 months’ corrected age at any of the 10 Canadian Neonatal Follow-Up Network clinics. The primary outcome was neurodevelopmental impairment at 18 to 24 months, defined as the presence of any of the following: cerebral palsy; Bayley-III cognitive, motor, or language composite score of <85; sensorineural or mixed hearing loss; and unilateral or bilateral visual impairment. Secondary outcomes included mortality, composite of mortality or neurodevelopmental impairment, significant neurodevelopmental impairment, and each component of the primary outcome. We compared outcomes between infants conceived through assisted reproductive technology and those conceived naturally, using bivariate and multivariable analyses after adjustment. Of the 4863 eligible neonates, 651 (13.4%) were conceived using assisted reproductive technology. Maternal age; education level; and rates of diabetes mellitus, receipt of antenatal corticosteroids, and cesarean delivery were higher in the assisted reproduction group than the natural conception group. Neonatal morbidity and death rates were similar except for intraventricular hemorrhage, which was lower in the assisted reproduction group (33% [181 of 546] vs 39% [1284 of 3318]; P=.01). Of the 4176 surviving infants, 3386 (81%) had a follow-up outcome at 18 to 24 months’ corrected age. Multivariable logistic regression adjusting for gestational age, antenatal steroids, sex, small for gestational age, multiple gestations, mode of delivery, maternal age, maternal education, pregnancy-induced hypertension, maternal diabetes mellitus, and smoking showed that infants conceived through assisted reproduction was associated with lower odds of neurodevelopmental impairment (adjusted odds ratio, 0.67; 95% confidence interval, 0.52–0.86) and the composite of death or neurodevelopmental impairment (adjusted odds ratio, 0.67; 95% confidence interval, 0.54–0.84). Conception through assisted reproductive technology was associated with decreased odds of a Bayley-III composite cognitive score of <85 (adjusted odds ratio, 0.68; 95% confidence interval, 0.48–0.99) and composite language score of <85 (adjusted odds ratio, 0.67; 95% confidence interval, 0.50–0.88). Compared with natural conception, assisted conception was associated with lower odds of adverse neurodevelopmental outcomes, especially cognitive and language outcomes, at 18 to 24 months’ corrected age among preterm infants born at <29 weeks’ gestation. Long-term follow-up studies are required to assess the risks of learning disabilities and development of complex visual-spatial and processing skills in these children as they reach school age.